Pengaruh Efek Samping Imunisasi terhadap Tingkat Kecemasan Ibu Balita - Fithrotuz Zakiyah; Lisus Setyowati; Homsiatur Rohmati (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
An adverse event following immunization (AEFI) are medical case which related to vaccine reactions, injection reactions, pharmacological effects, procedural in failure, coincidences or undetermined causal relationships. AEFI are also defined as a medical event following an unintended immunization that results in hospitalization or extension of hospitalization, permanent or significant disability and death, and causes unrest. This study aims of this study was to find out immunization side effects on the anxiety level of mothers who has toddler in the Cakru Community Health Center working area located in Jember.The research method used quantitative with correlational techniques by sample size of 51 people, and using the Chi Square test for analyze.From identificated of immunization on toddler, that was found if most of respondents got of immunization effects about 38 respondents (74.5%) and most of them respondents had mild low anxiety about 26 respondents (51%). The results bye Chi-Square test, it was found it p value<0.05, (p = 0.000) which was indicated, there was immunization side effects to anxiety level of mothers in the Cakru Health Center Work Area.Families and mothers are expected to participate health education about complete immunization and about the effects after getting immunization.